دراسة خصائص جبن الشنكليش في الساحل السوري ومقارنتها بمثيلاتها من بعض الأجبان العالمية - حرفوش محسن (Latakia University Journal -Biological Sciences Series, 2019)
هدف هذا البحث إلى دراسة أهم خصائص جبن الشنكليش لتحديد هويته ومقارنته ببعض الأجبان الواسعة الانتشار عالمياً, وذلك بإجراء عدد من التحاليل الكيميائية والجرثومية لعينات جمعت خلال عامي 2009 و2010 من مناطق مختلفة في الساحل السوري تشتهر في تصنيع هذا المنتج. أوضحت الدراسة التباين الكبير في التركيب الكيماوي للعينات وأن الشنكليش جبن نصف جاف منضج خارجياً بالخمائر والفطور بشكل أساسي وأن خصائص الإنضاج هي pH 6.14 ومعامل إنضاج 37.9 وحموضة حرة في المادة الدسمة 2.1% وهي قريبة جداً من أجبان الكاممبرت والروكفورت العالمية. كما أوضحت الدراسة أن الشنكليش فقير بالدهن (14.2%), وغني جداً بالبروتين (56.7%) بالنسبة للمادة الجافة, وأن كليهما تعرض لعملية هضم أنزيمي متقدم. بينت النتائج أن الشنكليش غني بالفوسفور (200-270 ملغ/100غ) الذي يبلغ ضعف الكالسيوم تقريباً (73-138مغ/100), وأن محتواه من الرصاص (0.47 ملغ/كغ) مطابق للمواصفة القياسية السورية والعالمية, ولكن محتواه من الكادميوم (0.1 ملغ/كغ) مرتفع جداً مقارنة بالأجبان العالمية, وكذلك من الألمنيوم (72.5 ملغ/كغ) وهذا ما يبين دور الأوعية المستخدمة في التصنيع. أخيراً, أوضحت النتائج أن الحمولة الجرثومية مرتفعة جداً حيث كان التعداد الكلي للجراثيم4.7 x 107/غ وأن جميع العينات مخالفة للمواصفة القياسية السورية بالنسبة لجراثيم الـ E.coli, كما بينت غياب جراثيم Staphylococcus aureus من جميع العينات المدروسة. The aim of this research is to study characteristics of Shankalish cheese in order to identify it and compare it with some internationally widespread cheeses. Several chemical and microbiological analysis were performed on samples collected during 2009 and 2010 from different Syrian coastal regions famous for this product. The study showed big variations in chemical composition of the samples, and that Shankalish is a semidry cheese ripened externally by yeasts and molds. Ripening coefficient (37.9) and other characteristics such as pH (6.14) and Free Fatty acids (2.1%) were similar to the international Camembert and Roquefort cheeses. The study indicated that Shankalish is poor in fat and very rich in protein (14.2% and 56.7% dry basis respectively). Both are subjected to advanced enzymatic activity. Results also showed that Shankalish is rich in phosphorus (200-270 mg/100g) which is about twice the amount of calcium (73-138 mg/100g), and that lead content (0.47 mg/kg) conforms to the Syrian and international standards. However, the contents of both cadmium and aluminum (0.1 and 72.5 mg/kg respectively) are very high. This may be a result of the containers usually used in the processing. Lastly, the results showed a very high microbial load (total count 4.7 x 107/g) and that St. aureus was not present in any sample, but all samples did not conform to the Syrian standards concerning E.coli.